Sanksi Administrasi Bagi Pelanggar Protokol Kesehatan Saat Pandemi Covid-19 - Bintang Natanael; Sharron Syallomeita; Irvin Atara (LPPM Institut Pendidikan Nusantara Global, 2026)
The COVID-19 pandemic has tested the effectiveness of the legal system and public awareness in complying with government regulations. This study aims to analyze the implementation of administrative sanctions for violations of health protocols during the COVID-19 pandemic and to assess their effectiveness in increasing public compliance. This research employs a normative legal method with a statute approach and a conceptual approach. Data were obtained through literature studies consisting of primary and secondary legal materials, then analyzed using a qualitative–deductive method. The results show that the imposition of administrative sanctions such as warnings, fines, community service, and license revocation has a strong legal basis and aligns with the principles of the rule of law and the maxim salus populi suprema lex esto. However, implementation in the field has not been optimal due to low legal awareness, weak supervision, and inconsistent law enforcement. Increasing legal socialization, continuous monitoring, and firm enforcement are needed to ensure the effectiveness of administrative sanctions as an instrument to prevent violations of health protocols.